Where does the interaction break down? The stakeholder map of health IT systems development and use in Finland - Susanna Martikainen; Mikko Korpela; Irmeli Luukkonen; Vilma Vainikainen (Finnish Social and Health Informatics Association, 2015)
Prior research shows that clinical users' experience of healthcare IT systems in Finland is poor. Research shows further that physicians are highly critical of the perceived lack of user participation in systems development, but developers of the same systems argue that they do work with users and are highly interested in their views. This study aimed at mapping the stakeholders involved in the user-developer interaction network, in order to identify the spots where the interaction breaks down. A method for depicting the healthcare landscape was adapted for depicting the healthcare IT systems development landscape. Experts selected through purposive sampling were interviewed to identify stakeholders and problems. Content analysis was used to categorise problems into development spots. A stakeholder map was drawn, consisting of 22 organization types, nine activities within them, and two groups of individuals. Seven development spots were identified, within and between the healthcare provider and the software provider but also related to other stakeholders. A significantly larger number of stakeholders are involved in healthcare IT system development than what was initially evident. They all influence the end-user experience in some way. It is not only the software product itself (whether with good or bad usability), but also several other factors that may affect user experience. Further research can now focus on what can be done and by whom to address the development spots.